The Academic Services during the Covid-19 Pandemic: Study on Five Service Quality Dimensions - Aldila Krisnaresanti; Lina Rifda Naufalin; Aldila Dinanti (Faculty of Economics and Business Universitas Jenderal Soedirman, 2022)
This study aims to analyze the level of quality of educational services during the COVID-19 pandemic, including the dimensions of direct evidence, reliability, responsiveness, assurance, and empathy. This research is descriptive research and survey research. Research respondents are students of the Economic Education study program at Jenderal Sudirman University. The study results indicate that the five dimensions of the quality of academic services as a whole are considered sufficient. So it can be concluded that the quality of academic services provided by the Economic Education Study Program of the Faculty of Economics and Business Unsoed during the Covid-19 pandemic is considered quite good and can be improved to meet the quality of excellent academic services.